The Gender Role in Agroforestry Management in Sungai Langka Village, Gedong Tataan District, Pesawaran Regency, Lampung Province - Pasaribu, Septo Widodo; Kaskoyo, Hari; Safe’i, Rahmat (Journal of Sylva Indonesiana, 2019)
Agroforestry has been developed for community welfare. Agroforestry is a combination of forestry crops and agricultural crops. Agroforestry management can not be separated from the active role of the community so that it is closely related to the role of men and women (gender) in managing agroforestry. Sampling was carried out in September 2018 using the simple random sampling method. The method of data collection is interview using a questionnaire. Data was tabulated and analyzed descriptively qualitatively using Harvard gender model analysis. Agroforestry management activities carried out by farmers in Sungai Langka Village include pre-harvest, planting, maintenance, harvesting and transport activities and post-harvest activities (post-harvest activities and marketing). The results showed men who opposed pre-harvest activities with a percentage of 93.95%. This is because these activities are heavy work and require a large amount of energy so that they are suitable for work by men. Women dominate pre-harvest activities such as post-harvest and marketing activities with a percentage of 93.02%. This concerns this work is a light work and can be done while taking care of the household.